Metagenomic insights into bacterial communities and functional genes associated with texture characteristics of Kazakh artisanal fermented milk Ayran in Xinjiang, China. (February 2023) - Kuerman, Malina; Wang, Rui; Zhou, Yu; Tian, Xiaoying; Cui, Qingyu; Yi, Huaxi; Gong, Pimin; Zhang, Zhe; Lin, Kai; Liu, Tongjie; Zhang, Lanwei
Graphical abstract: Highlights: Metagenomics revealed the microbial diversity and functional genes of Ayran . Ayran of different regions showed varying texture characteristics. Lactobacillus helveticus was the dominant species in Ayran with high hardness. Pip and pepE significantly improved the coagulation quality of fermented milk. Abstract: The complex microflora of traditional fermented milk is crucial to milk coagulation mainly through acid and protease production; however, it is still unclear which microbes and proteases significantly influence the texture of Ayran, a Kazakh artisanal fermented milk in Xinjiang, China. In this study, fifty-nine samples of Ayran were collected and investigated on texture properties. Finally, six Ayran samples with different texture features were screened out, and the taxonomic and functional attributes of their microbiota were characterized by metagenomics. The results showed that the hardness of the fermented milk in Yili Kazakh Autonomous Prefecture was significantly higher than that in other pasture areas. Lactobacillus and Lactococcus were the core genera that affected the coagulation quality of milk. Furthermore, we found that the proline iminopeptidase pip (EC 3.4.11.5) gene of Lactobacillus helveticus and Limosilactobacillus fermentum and the dipeptidase E pepE (EC 3.4.13.21) gene of Lactococcus lactis were most associated with the coagulation quality of fermented milk. Furthermore, positive correlations were observed among the hardness of fermented milk, the activity of the proteases, and the corresponding functional gene expressions.